Care satisfaction, hope, and life functioning among adults with bipolar disorder: data from the first 1000 participants in the Systematic Treatment Enhancement Program. - Morris, C; Miklowitz, D; Wisniewski, SR; Giese, A; Thomas, MR; Allen, M (2005)
OBJECTIVE: The Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) is designed to evaluate the longitudinal outcome of patients with bipolar disorder. The STEP-BD disease-management model is built on evidence-based practices and a collaborative care approach designed to maximize specific and nonspecific treatment mechanisms. This prospective study examined the longitudinal relationships between patients' satisfaction with care, levels of hope, and life functioning in the first 1000 patients to enter STEP-BD. METHODS: The study used scores from the Care Satisfaction Questionnaire, Beck Hopelessness Scale, Range of Impaired Functioning Tool, Young Mania Rating Scale, and Montgomery-Asberg Depression Rating Scale at 5 time points during a 1-year interval. Analyses tested mediational pathways between care satisfaction, hope, and life functioning, depression, and mania using mixed-effects (random and fixed) regression models. RESULTS: Increases in care satisfaction were associated with decreased hopelessness (P < .01) but not related to symptoms of depression or mania. Similarly, decreased hopelessness was associated with better life functioning (P < .01) but not related to symptoms of depression or mania. Depression was independently associated with poorer life functioning (P < .0001). CONCLUSIONS: This study provided support for the hypothesized mediational pathway between care satisfaction, hopelessness, and life functioning. Findings suggest that providing care that maximizes patient hope may be important. By so doing, patients might overcome the learned helplessness/hopelessness that often accompanies a cyclical illness and build a realistic illness-management strategy.